2022
DOI: 10.1007/s10803-022-05525-y
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Learning Through Online Video-Based Instruction for an Autistic Child

Abstract: The purpose of this study was to examine the effectiveness of a video modeling (VM) intervention package (including virtual manipulatives and error correction) delivered via synchronous, virtual environment to teach the mathematics skills of addition, number comparison, and subtraction to a five-year old autistic child. Using a multiple probe across skills design of a single-case experimental design, we examined whether a causal relation existed between the intervention and the child’s improved accuracy of mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…The researchers found a functional relation and concluded virtual manipulatives were more engaging to the students than concrete manipulatives. Yakubova et al (2022) found an elementary student with autism improved in their mathematical accuracy of addition, subtraction, and number comparison following an intervention package consisting of virtual manipulative, video modeling, and error correction. Finally, Root et al (2017) also found student success with virtual manipulatives, as well as concrete manipulatives, when implemented as part of a intervention package involving MSBI for three elementary students with IDD.…”
Section: Research On Virtual Manipulativesmentioning
confidence: 96%
“…The researchers found a functional relation and concluded virtual manipulatives were more engaging to the students than concrete manipulatives. Yakubova et al (2022) found an elementary student with autism improved in their mathematical accuracy of addition, subtraction, and number comparison following an intervention package consisting of virtual manipulative, video modeling, and error correction. Finally, Root et al (2017) also found student success with virtual manipulatives, as well as concrete manipulatives, when implemented as part of a intervention package involving MSBI for three elementary students with IDD.…”
Section: Research On Virtual Manipulativesmentioning
confidence: 96%
“…Studies on instructional techniques in providing mathematics instruction to autistic students using VBI, virtual manipulatives, and games have been focused mostly on inperson instruction (e.g., Hughes & Yakubova, 2019;Satsangi & Bofferding, 2017;Yakubova et al, 2020). Research on online instructional practices for teaching autistic students and students with other disabilities started to emerge in the last couple of years due to the onset of pandemic (Bouck et al, 2022a(Bouck et al, , 2022bYakubova et al, 2022). Though in-person instruction has since resumed in schools, the public health crisis demonstrated the need to examine and identify evidence-based practices in online instruction in order to be ready to accommodate students in the future, not only in case of public health emergencies, but also in case of student illnesses, e.g., seasonal flu, allergies, etc., that may prevent them from physically attending an in-person class or for students who are homeschooled.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, evidence on instructional strategies to support mathematics learning in online instructional contexts is scarce. While intervention research on online instructional practices started to emerge with the onset of the COVID-19 pandemic (e.g., Bouck & Long, 2021; Yakubova et al, 2022), students with disabilities have been participating in online or hybrid education long before the pandemic (e.g., Burdette et al, 2013). Research focusing on the online education needs of students with disabilities have examined various factors related to online education (e.g., parental and child perceptions and experiences; Smith et al, 2016; Tonks et al, 2021) with limited evidence on the types of instructional practices that can be effectively used to support the online instruction (Vasquez III & Serianni, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They attribute the challenges to limited understanding and training on the appropriate interventions to assist students with autism to overcome their learning impairments (Bullen et al, 2022). Teachers can address the disparities between students in regular instructions and their peers with MLD and autism by implementing evidence-based interventions, such as Modified Schema-Based Instruction (MSBI), which is a problem-solving heuristic approach (Root et al, 2022;Yakubova et al, 2022). students with autism are similar to students with MLD because their achievement is usually low when teachers fail to complement directed pedagogy with student-centered learning (Griffiths et al, 2021;Schnepel & Aunio, 2021;Apanasionok et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%